Application of hierarchical management based on bleeding risk assessment in patients with catheter-directed thrombolysis for treatment of lower extremity deep venous thrombosis (出血风险管理在下肢深静脉血栓形成导管接触性溶栓治疗中的应用) - LIU Jiaying (刘佳莺); ZHANG Ting (张婷) (中西医结合护理)
Objective To analyze the application of hierarchical management based on bleeding risk assessment in patients with catheter-directed thrombolysis for treatment of lower extremity deep venous thrombosis (DVT). Methods Totally 100 patients requiring catheter-directed thrombolysis for treatment of lower extremity DVT were selected as the research objects, and they were randomly divided into the control group and the observation group, with 50 cases in each group. The control group received routine nursing, while the observation group received hierarchical nursing management based on bleeding risk assessment. The therapeutic effectiveness outcomes (patency rate, relief of lower extremity edema and treatment effect) and therapeutic safety outcomes (incidences of mild bleeding and severe bleeding) were measured and compared between two groups. Results The proportion of patients with patency rate≥50% and with relief rate of lower extremity edema≥50% in the observation group were higher than those in the control group, respectively (P＜0. 01). The therapeutic effective rate in the observation was higher than that in the control group(P＜0. 05). The incidences of mild bleeding and severe bleeding in the observation was lower than those in the control group, respectively(P＜0. 05). Conclusion The implementation of hierarchical management based on bleeding risk assessment can effectively improve the treatment effect of catheter-directed thrombolysis and reduce the incidence of bleeding complications. (目的 分析出血风险管理在下肢静脉血栓形成(DVT)患者导管接触性溶栓治疗中的应用。方法 选取2019年1月—2020年12月在医院血管外科住院治疗的100例患者为研究对象, 按照随机数字分组分为对照组和观察组, 各50例。患者均接受导管接触性溶栓治疗, 对照组给予常规专科护理, 观察组按照出血风险分级管理方案进行护理。比较两组患者静脉通畅率、下肢消肿率、治疗效果等治疗有效性指, 比较两组患者轻微出血率、严重出血率等治疗安全性指标。结果 观察组患者静脉通畅率≥50%及大腿、小腿消肿率≥50%的比例均高于对照组, 差异有统计学意义(P＜0. 01); 观察组治疗效果评价优于对照组, 差异有统计学意义(P＜0. 05)。观察组轻微出血、严重出血发生率低于对照组, 差异有统计学意义(P＜0. 05)。结论 在DVT患者导管接触性溶栓治疗中实施出血风险分级管理方案, 可以有效提高治疗效果, 降低患者出血并发症的发生风险。)